2021
DOI: 10.1016/j.wasman.2021.02.049
|View full text |Cite
|
Sign up to set email alerts
|

Temperature phased anaerobic digestion (TPAD) of organic fraction of municipal solid waste (OFMSW) and digested sludge (DS): Effect of different hydrolysis conditions

Abstract: Hydrolysis is the most critical stage in high solids Temperature Phased Anaerobic Digestion (TPAD). In this paper two different Organic Fraction of Municipal Solid Waste (OFMSW) types were tested in co-digestion with Digested Sludge (DS) at different temperatures: 37, 55 and 65 °C. Volatile fatty acids (VFAs), soluble chemical oxygen demand (CODs) and Biochemical Methane Production (BMP) were measured and calculated after 0, 24, 48 and 72 h hydrolysis. The results showed that both the BMP and the methane produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 52 publications
(55 reference statements)
0
14
0
Order By: Relevance
“…It should be remembered that NO 2 and CO are gases that are harmful to human health, as they are extremely carcinogenic (Cetin, 2016;Oliveira et al, 2021;Maharjan et al, 2022). CH 4 primarily originates from volcanic activities, in addition to the degradation of organic residues in anoxic environments (Amodeo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It should be remembered that NO 2 and CO are gases that are harmful to human health, as they are extremely carcinogenic (Cetin, 2016;Oliveira et al, 2021;Maharjan et al, 2022). CH 4 primarily originates from volcanic activities, in addition to the degradation of organic residues in anoxic environments (Amodeo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The correlations were considered statistically significant at a 95% confidence interval (a < 0.05). The authors of [42] also proved that TPAD showed a better performance in terms of methane production of up to 20% in comparison to the single-stage MAD.…”
Section: Anaerobic Digestion Performancementioning
confidence: 90%
“…The authors of [45] stated HRT to be a crucial parameter that can influence the efficiency of AD, and an HRT of 30 days allows all types of AD to become more or less the same in terms of biogas production, which makes the more energy-demanding TAD and TPAD less economically interesting. The authors of [42,46] underlined that the first stage of TPAD was the most efficient at 2-3 days, when the total HRT was less than 20 days.…”
Section: Anaerobic Digestion Performancementioning
confidence: 99%
“…Anaerobic digestion (AD) technology allows the treatment of the organic fraction of municipal solid waste (OFMSW) and the production of methane‐rich biogas and fertilizer for agricultural use 9,10 . The large‐scale implementation of AD of the OFMSW, of which food waste (FW) represents a significant part, is a challenge for dissemination of the technology, especially owing to the low biodegradation associated with the presence of lignocellulosic compounds in the solid phase 11,12 .…”
Section: Introductionmentioning
confidence: 99%